Analyzing the Determinants of Purchase Intention in E-commerce: Evidence from Bukalapak Users in Pekanbaru - Tyas, Rara Claudia Kusumaning; Noviasari, Henni; Siregar, Prima Andreas (West Science Business and Management, 2025)
This study investigates the determinants of purchase intention in e-commerce, focusing on Bukalapak users in Pekanbaru, Indonesia. The research examines the influence of electronic word-of-mouth (eWOM), brand image, and consumer trust on purchase intention. A sample of 150 respondents was selected using non-probability sampling and purposive sampling techniques. Data were collected through questionnaires, observations, and documentation, and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the SMART-PLS application. The results indicate that eWOM and brand image directly influence purchase intention and consumer trust. Consumer trust also directly affects purchase intention. Furthermore, eWOM and brand image indirectly influence purchase intention through consumer trust as a mediating variable. The findings suggest that eWOM and brand image play crucial roles in shaping consumer perceptions and building trust, which ultimately drives purchase intention in the context of e-commerce. The study highlights the importance of delivering strong and convincing information through eWOM and establishing a positive brand image to effectively increase consumer trust and purchase intention. The research contributes to the understanding of consumer behavior in e-commerce and provides insights for Bukalapak to enhance its marketing strategies and address the challenges of declining visitor numbers and purchase intentions.